Effect of intratracheal dexmedetomidine combined with ropivacaine on postoperative sore throat: a prospective randomised double-blinded controlled trial - Jingyi Niu; Rui Hu; Na Yang; Yan He; Hao Sun; Rende Ning; Junma Yu (BMC Anesthesiology, 2022)
Abstract Background The present study aimed to investigate whether intratracheal dexmedetomidine combined with ropivacaine reduces the severity and incidence of postoperative sore throat after tracheal intubation under general anaesthesia. Methods Two hundred patients with American Society of Anaesthesiologists physical status I-II who were subjected to general anaesthesia were randomly divided into four groups, namely, Group D, Group R, Group DR and Group S; these groups received intratracheal dexmedetomidine (1 µg/kg), 0.8% ropivacaine (40 mg), dexmedetomidine (1 µg/kg) combined with 0.8% ropivacaine (40 mg) and normal saline before endotracheal intubation, respectively. The primary outcomes were the incidence and grade of sore throat and hoarseness at 2 h and 24 h after surgery. Moreover, the modified Observer's Assessment of Alertness/Sedation Scale results were recorded at each time point. The secondary outcomes were intraoperative haemodynamic fluctuations, intraoperative anaesthetic drug requirements, and adverse reactions during and after surgery. The patients’ vital signs before induction, before superficial anaesthesia, after superficial anaesthesia, before intubation, after intubation, and 1 min after intubation were recorded. The use of anaesthetic drugs and occurrence of adverse effects were also recorded. Results The incidence and severity of sore throat were significantly lower in Group DR than in the other three groups 2 h after the operation, but they were only significantly lower in Group DR than in the control group 24 h after the operation. Moreover, compared with Group S and Group D, Group DR exhibited more stable haemodynamics during intubation. The doses of remifentanil and propofol were significantly lower in Group DR than in the other groups. Conclusion The combined use of dexmedetomidine and ropivacaine for surface anaesthesia before intubation significantly reduced the incidence and severity of postoperative sore throat. This treatment also decreased anaesthetic drug requirements and intraoperative haemodynamic fluctuations and caused no adverse effects. Trial registration This clinical research was registered at the Chinese Clinical Trial Registry (ChiCTR1900022907, Registration date 30/04/2019).